2020
DOI: 10.3329/bjo.v25i2.45210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes Mellitus on Hearing

Abstract: Background: Diabetes mellitus (DM) is a chronic systemic disease characterized by hyperglycemia due to absolute or relative deficiency of insulin and affects several systems including hearing. It was evidenced that hearing loss is twice as common in people with diabetes in comparison to other non-diabetic individuals. Although there is no epidemiological information are available in Bangladesh, but it can assume that the number would not be less. Methods: This study was a hospital based case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…8 This is also supported by a study by Bener et al 5 , which showed a high risk of SNHL hearing loss in patients with T2DM and hypertension. Similar findings were found by Ghosh et al 3 that the duration of T2DM and HbA1c levels had a significant relationship with the incidence of SNHL. The conditions that cause SNHL are multifactorial, with early detection will greatly affect the prognosis, quickly making a diagnosis will improve the quality of life of T2DM patients.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…8 This is also supported by a study by Bener et al 5 , which showed a high risk of SNHL hearing loss in patients with T2DM and hypertension. Similar findings were found by Ghosh et al 3 that the duration of T2DM and HbA1c levels had a significant relationship with the incidence of SNHL. The conditions that cause SNHL are multifactorial, with early detection will greatly affect the prognosis, quickly making a diagnosis will improve the quality of life of T2DM patients.…”
Section: Introductionsupporting
confidence: 91%
“…Various factors influence the incidence of SNHL, such as old age, gender, family history, smoking and diabetes. 1,3 Sensorineural deafness in a previous study was more common in patients with diabetes than in non-diabetics, with the degree of hearing loss correlated with disease progression. This may be due to the occurrence of microangiopathic complications in the inner ear.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is speculated that the vascular and neuronal changes occurring as a result of diabetes mellitus could lead to the thickening of the basal membrane of the capillaries of stria vascularis, demyelination of the nerve of the cochlea and atrophy of spiral ganglion; all of which, alone or in combination, would lead to hearing loss. 3,9,11,13 Other factors which have been implicated in the pathogenesis of sudden sensorineural hearing loss like viral inflammatory conditions of the labyrinth, autoimmune conditions damaging the cochlear apparatus or any degree of compromise in the blood flow due to microvascular diseases respond well to corticosteroid therapy. 14,15 Systemic administration of corticosteroids has been shown to have very good efficacy especially if given early in the course of the disease as has been shown in the studies done by a number of researchers.…”
Section: Discussionmentioning
confidence: 99%
“…In type 1 diabetes there is inadequate synthesis of insulin by the pancreas while in type 2 diabetes the sensitivity of cells to insulin is decreased. 9 Researches show that the incidence of sudden sensorineural hearing loss in patients with diabetes mellitus increases with an increase in the severity and duration of diabetes mellitus, and also with the presence of other risk factors such as hypertension, dyslipidemia, renal disorders, obesity, smoking, alcoholism etc. 3 Also the prognosis of hearing loss is worse in patients with more risk factors.…”
Section: Introductionmentioning
confidence: 99%